2023
DOI: 10.3390/plants12183282
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Plastics on Plant Development: Recent Advances and Future Research Directions

Enikő Mészáros,
Attila Bodor,
Etelka Kovács
et al.

Abstract: Plastics have inundated the world, with microplastics (MPs) being small particles, less than 5 mm in size, originating from various sources. They pervade ecosystems such as freshwater and marine environments, soils, and the atmosphere. MPs, due to their small size and strong adsorption capacity, pose a threat to plants by inhibiting seed germination, root elongation, and nutrient absorption. The accumulation of MPs induces oxidative stress, cytotoxicity, and genotoxicity in plants, which also impacts plant dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
(132 reference statements)
1
0
0
Order By: Relevance
“…One seedling was planted per pot in one of three concentrations: 0 (control), 0.1% (0.5 g w/w of polyester fibres) or 1% (5 g w/w of plastic fibres) after germinating in cotton wool, giving a total of 200 pots per treatment. The concentrations of polyester microfibres were similar to those which reported noticeable changes in plant responses (Yu et al, 2021;Jia, 2023;Mészáros et al, 2023). As plastic pollution continues, investigating high concentrations could help to represent future scenarios .…”
Section: Planting Conditionssupporting
confidence: 68%
“…One seedling was planted per pot in one of three concentrations: 0 (control), 0.1% (0.5 g w/w of polyester fibres) or 1% (5 g w/w of plastic fibres) after germinating in cotton wool, giving a total of 200 pots per treatment. The concentrations of polyester microfibres were similar to those which reported noticeable changes in plant responses (Yu et al, 2021;Jia, 2023;Mészáros et al, 2023). As plastic pollution continues, investigating high concentrations could help to represent future scenarios .…”
Section: Planting Conditionssupporting
confidence: 68%
“…Studies have been carried out to understand the impact of MPs on lower organisms like microalgae [8], coral reefs [9], and zooplankton [10]. Apart from this, investigations have revealed that honeybees [11], freshwater and marine organisms [12,13], slugs, soil [14], plants [15], moss [16], and even the human body [17] can become contaminated by MPs due to increasing ubiquitous plastic consumption. Moreover, soil and water bodies can also host MPs to form MP sinks, leading to their leakage into the food chain [18].…”
Section: Introductionmentioning
confidence: 99%